Causes of death through verbal autopsy: findings from a sub-study of single dose oral cholera vaccination in urban Dhaka, Bangladesh - Md. Taufiqul Islam; Md. Mazharul I. Zion; Md. Arifuzzaman Khan; Zahid H. Khan; Faisal Ahmmed; Shamim Ahmed; Azimuddin Ahmed; Afroza Akter; Fahima Chowdhury; Amit Saha; Nirod C. Saha; Deok R. Kim; et al. (Journal of Global Health Reports)
# Background